Permeation of Phytochemicals of Selected Psychoactive Medicinal Plants across Excised Sheep Respiratory and Olfactory Epithelial Tissues - Anja Haasbroek-Pheiffer; Alvaro Viljoen; Jan Steenekamp; Weiyang Chen; Josias Hamman (MDPI AG, 2023)
The intranasal route of drug administration offers an opportunity to bypass the blood-brain barrier and deliver compounds directly into the brain. Scientific evidence exists for medicinal plants (e.g., Centella asiatica and Mesembryanthemum tortuosum) to treat central nervous system conditions such as anxiety and depression. The ex vivo permeation of selected phytochemicals (i.e., asiaticoside and mesembrine) has been measured across excised sheep nasal respiratory and olfactory tissue. Permeation studies were conducted on individual phytochemicals and C. asiatica and M. tortuosum crude extracts. Asiaticoside exhibited statistically significantly higher permeation across both tissues when applied alone as compared to the C. asiatica crude extract, while mesembrine permeation was similar when applied alone or as M. tortuosum crude extract. Permeation of all the phytocompounds was similar or slightly higher than that of the drug atenolol across the respiratory tissue. Permeation of all the phytocompounds was similar to or slightly lower than that of atenolol across the olfactory tissue. In general, the permeation was higher across the olfactory epithelial tissue than across the respiratory epithelial tissue and therefore showed potential for direct nose-to-brain delivery of the selected psychoactive phytochemicals.